Municipal Solid Waste Generation, Composition, and Management in Nigeria: A 25-Year Secondary Data Review - Alamu, Abideen Salawu (Journal of Sustainability and Environmental Management, 2025)
Municipal solid waste (MSW) management in Nigeria poses growing environmental and public health challenges due to rapid urbanization and population growth. This study applied a secondary data analysis approach, synthesizing peer-reviewed studies, institutional reports, and datasets published between 2000 and 2025 to examine temporal trends and spatial variations in waste generation and management. Results showed a strong correlation (r ≈ 0.78) between urbanization and per capita waste generation, which ranged from 0.35–1.02 kg/person/day (mean ≈ 0.6). Total national waste increased from about 25,000 tonnes/day in 2000 to 35,000 tonnes/day in 2025, with organic waste (≈55%) predominating. Open dumping remains the main disposal method (≈80%), while recycling and composting are limited. The discussion highlights that urban growth, though driving waste increase, also creates opportunities for circular economy adoption. The study concludes that strengthening policy enforcement, financing, and community participation is essential for achieving sustainable and health-conscious waste management in Nigeria.